Koli Calling '20: Proceedings of the 20th Koli Calling International Conference on Computing Education Research 2020
DOI: 10.1145/3428029.3428050
|View full text |Cite
|
Sign up to set email alerts
|

Should Explanations of Program Code Use Audio, Text, or Both? A Replication Study

Abstract: Studies in educational psychology suggest that people learn better when visual learning materials are accompanied by audio explanations rather than textual ones. Research on how this modality effect applies to computing education is scarce and inconclusive. We explore whether modality of instruction affects learning from videos that use a series of example programs to explain how variables work in Python. Learners (n=186) were crowdsourced from the internet and randomized in three groups, who received explanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 96 publications
2
11
0
1
Order By: Relevance
“…We found no support for there being a modality effect or verbal redundancy effect when Dijkstra's algorithm is taught using visualizations accompanied by textual and/or auditory explanations. This result is analogous to the null results obtained previously by Morrison [44] and Zavgorodniaia et al [69] on program code accompanied by explanations in different modalities. Compared to findings outside of CER, our result contrasts with the studies that have found evidence of a modality effect but is far from being unique in finding no support for the effect (see, e.g., [24,53]).…”
Section: Visual Algorithm Simulation Tasksupporting
confidence: 91%
See 4 more Smart Citations
“…We found no support for there being a modality effect or verbal redundancy effect when Dijkstra's algorithm is taught using visualizations accompanied by textual and/or auditory explanations. This result is analogous to the null results obtained previously by Morrison [44] and Zavgorodniaia et al [69] on program code accompanied by explanations in different modalities. Compared to findings outside of CER, our result contrasts with the studies that have found evidence of a modality effect but is far from being unique in finding no support for the effect (see, e.g., [24,53]).…”
Section: Visual Algorithm Simulation Tasksupporting
confidence: 91%
“…Morrison [44] suggested that a possible explanation for her results was the learning materials' excessive complexity. Zavgorodniaia et al [69] replicated Morrison's study using a less challenging video tutorial and a larger and different cohort of learners. They crowdsourced 186 paid participants with little to no self-reported programming experience and randomly assigned each to Audio, Text, or Both.…”
Section: 22mentioning
confidence: 80%
See 3 more Smart Citations